Strategi Pembelajaran Bahasa Inggris Mahasiswa Mahad IAIN Bukittinggi - Leli Lismay; Zubaidah Zubaidah (Jurnal Educative: Journal of Educational Studies, 2019)
Living in a dormitory is a must for the first year students of IAIN Bukittinggi, especially English Education Department. They followed some rules in their daily activities there. They also have some activities including alqur’an recitation, leaderhip, Arabic and English training. Based on the phenomenon above, this research analyzed the use of language learning strategies by the students who lived in mahad. Qualitative analysis was used to find the English language learning strategy and the factors support and obstales face by the stde the used of language learning strategy itself. The results showed that most of the students used affective strategy more in their English language learning. It explained that good attitude and motivation taking a big part in the language learning strategies which brough the students to the deeper understanding of using English for their daily conversation. Then, some factors like the ability to motivate their self in learning English and environment became obstacles in mastering English in mahad IAIN Bukittinggi. This can be anticipated by arranging their scedule well during the day of their learning.Tinggal di asrama merupakan suatu keharusan bagi mahasiswa tahun pertama di IAIN Bukittinggi, khususnya jurusan Bahasa. Mereka mengikuti dan mematuhi beberapa aturan yang ditetapkan Asrama untuk kegiatan mereka sehari-hari. Mereka juga mengikuti beberapa kegiatan tambahan seperti; menghafal alqur’an, kepemimpinan, pelatihan Bahasa Arab dan Bahasa Inggris. Berdasarkan fenomena tersebut maka penelitian ini menganalisa penggunaan strategi pembelajaran bahasa oleh mahasiswa yang tinggal di Mahad. Analisa kualitatif digunakan untuk menemukan strategi pembelajaran bahasa dan faktor pendukung serta kesulitan yang dihadapi siswa dalam mempelajari bahasa. Hasil penelitian ini menunjukkan bahwa kebanyakan mahasiswa menggunakan strategi afektif dalam pembelajaran bahasa mereka. Hal ini menjelaskan bahwa sikap yang baik dan motivasi untuk berpartisipasi dalam penggunaan bahasa membawa mereka kepada pemahaman penggunaan Bahasa Inggris untuk percakapan sehari-hari. Kemudian, beberapa faktor seperti kemampuan memotivasi diri dan lingkungan menjadi kendala dalam menguasai Bahasa Inggris di Mahad IAIN Bukittinggi. Hal ini bisa diantisipasi dengan mengatur jadwal dengan baik untuk belajar.